Investigation of Anti Inflammatory Activity of Triphala Hydrogels in Carrageenan Induced Paw Edema Model - Kalva, Sireesha; Andhi, Neha; Yenni, Ramya Sree; Ganesh, P. Sai; Madhu, A.; Nihal, M. (Asian Journal of Pharmaceutical Research and Development, 2023)
Inflammation is a reaction of a living vascularized tissue to an injury, conventional or synthetic drugs used in the treatment of inflammatory diseases are inadequate, it sometimes has serious stroke effects. So, number of herbal medicines are recommended for the treatment of inflammation that has no side effects. Hence our study focused to investigate bioactive compounds for anti-inflammatory activity. Folk medicine and ethnopharmacological data can provide a broad range of plants with promising anti-inflammatory activity. Triphala, an ayurvedic formula composed of three different plants. Terminalia chebula Retz., Terminalia bellerica Roxb(Combretaceae) and Phyllanthus emblica L is widely used for various microbial infections. Triphala is now evaluated for its anti-inflammatory action. Triphala is formulated into a hydrogel of different concentrations and is evaluated for in-vitro anti-inflammatory activity by membrane stabilization method at 100, 250 and 500 mg/ml and in-vivo evaluation is done by Carrageenan -induced paw edema method. The results obtained are compared with standard NSAID diclofenac hydrogel. The prepared hydrogel of triphala showed a dose-dependent anti-inflammatory potential in in-vivo and in-vitro methods which provide scientific basis for anti-inflammatory activity of Triphala.